Alcoholism model of drug dependency - CRM Educational Films (Del Mar, Calif. : CRM/McGraw-Hill Films, 1972)
This film examines the problem of alcoholism in the society. A computer serves as the introductory medium, programmed to play a series of videotaped vignettes depicting the mental and physiological characteristics of successive state of intoxication.
Bahan rosak - 17 Jan 08
Keywords: Alcoholism -- Physiological aspects; Alcohol -- Physiological effect